Willingness to Pay Water User Assosiation (WUA’s) in the Water Resource Conservation (Study Case in Boro’s Irrigation Area ) - Endah Kusumaningrum; Nuddin Harahab; Bagyo Yanuwiadi (Graduate Program, 2016)
The degradation of watershed, especially the damages on the upstream may affect hydrological conditions on the downstream area which is the irrigation system. Through payments for environmental services, the result of the rehabilitation of irrigation can be used by communities on the upstream area for conservation so that the availability of water for farmers downstream are available. The purpose of this study is to analyze the perception of WUA’s to the conservation of water resources, observe the value of Willingness to Pay (WTP) of WUA’s and analyze the factors that form WUA’s toward the conservation of water resources. The variables of this research were the socioeconomic variable of WUA’s and their perception of the water resources conservation. The study was conducted at Boro’s Irrigation Area in Purworejo with a total sample of 44 WUA’s in the first planting season in 2016. There are three methods for data analysis in this study, namely (1) descriptive analysis with content analysis to analyze the perception of the WUA’s to the water resources conservation; (2) Contingent Valuation Method Approach (CVM) to determine the price of willingness to pay by WUA’s in the water resources conservation; (3) Factor Analysis to analyze the relevant factors that affect the willingness to pay (WTP) of WUA’s in the water resources conservation. The result of content analysis show that WUA’s perception about water resources conservation is still need to be raised with education about the importance of water resource conservation. Estimated average WTP of WUA’s in the water resources conservation is IDR 88,438 per year. The total value WTP in Boro area could reach IDR 461.340.000,- Factors that affect their shared WTP simultaneously are age, farming tenure, income, education, land ownership, land coverage and perceptions of the water resources conservation, while the number of family dependents does not significantly affect their WTP are farming experience, knowledge about the condition of the upstream, income, knowledge about the changing quality of irrigation, skills utilization of irrigation, and conservation efforts.Key words: Payment for Environmental Services, perception, Willingness to pay (WTP), Water User’s Assosiation (WUA’s), water resources conservation,